The effectiveness of prenatal exercise on leg swelling in third-trimester pregnant women: A literature review - Ni Wayan Sulistia Devi; Ni Luh Putu Sri Erawati; Ni Wayan Suarniti (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Leg swelling (edema) is a common complaint among third-trimester pregnant women due to fluid retention and impaired venous return. Prenatal exercise is a safe nonpharmacological intervention that can help reduce leg edema. Purpose: To determine the effectiveness of prenatal exercise on leg swelling in third-trimester pregnant women based on previous research findings. Method: This study employed a literature review method, with articles retrieved from the PubMed, Google Scholar, and ScienceDirect databases from 2021 to 2026. Inclusion criteria included original research articles on prenatal exercise or physical activity regarding leg edema in third-trimester pregnant women. Article selection followed the PRISMA flowchart, resulting in 9 eligible articles. Results: The review findings indicate that prenatal exercise is effective in reducing leg swelling in third-trimester pregnant women. Prenatal exercise helps improve blood circulation, enhance venous return, improve vascular function, and reduce fluid retention in the lower extremities. Additionally, prenatal exercise improves physical comfort and quality of life for pregnant women. Conclusion: Prenatal exercise is effective as a nonpharmacological intervention to reduce leg edema in third-trimester pregnant women and can be recommended in antenatal care.